KASUS ASIMETRI INFORMASI BPJS KESEHATAN DALAM PERSPEKTIF EKONOMI KEYNESIAN BARU (JEB17 : Jurnal Ekonomi dan Bisnis, 2023)
Health Insurance is important for the community. In Indonesia, a special institution has been created that houses all health insurance problems, namely BPJS Kesehatan. Data shows that in 2021, 229,51 million Indonesians have been covered by BPJS Kesehatan. The establishment of BPJS Kesehatan Indonesia turned out to cause new problems. There is an asymmetry of information that occurs because the beneficiaries of BPJS Kesehatan have more information than BPJS Kesehatan Indonesia. World economist George A. Akerlof, who is an economic figure of the new Keynesian school, stated that information asymmetry is a gap in information obtained by both parties when conducting a transaction or an activity. This study aims to analyze the case of information asymmetry of BPJS Kesehatan Indonesia according to the economic perspective of Keynesian Baru. The research method used is a qualitative approach with a descriptive method. Results of the analysis show that the occurrence of cases of information asymmetry at the BPJS Kesehatan Indonesia Institution is due to data asynchrony and the mindset of the community which is still not aware of health issues and willingness to pay. The impact of the information asymmetry case is the closure of BPJS Kesehatan Indonesia products due to the continued deficit in the balance sheet. Keywords: Asymmetric Information, BPJS Kesehatan, Keynesian Baru